A novel approach to predict the risk in Dengue Hemorrhagic Fever (DHF) using bioelectrical impedance analysis - Abdul Rahim, Herlina (Penerbit UTM, 2010)
Dengue infections are due to several types of dengue viruses. Initially, it was difficult to differentiate dengue fever since its characteristics is similar to some other diseases. An early study reported that between the years 1780 to 1940, a unique characteristic associated with dengue-like illness was the relatively infrequent but often large epidemics.